Ethanol, Acetaldehyde and Estradiol Affect Growth and Differentiation of Rhesus Monkey Embryonic Stem Cells - VandeVoort, Catherine A. (2011)
BACKGROUND: The timing of the origins of fetal alcohol syndrome have been difficult to determine, in part because of the challenge associated with in vivo studies of the peri-implantation stage of embryonic development. Because embryonic stem cells (ESCs) are derived from blastocyst stage embryos, they are used as a model for early embryo development. METHODS: Rhesus monkey ESC lines (ORMES-6 and -7) were treated with 0, 0.01%, 0.1%, or 1.0% ethanol, 1.0% ethanol with estradiol or 0.00025% acetaldehyde with or without estradiol for 4 weeks. RESULTS: Although control ESCs remained unchanged, abnormal morphology of ESCs in the ethanol and acetaldehyde treatment groups was observed before 2 weeks of treatment. Immunofluorescence staining of key pluripotency markers ( TRA-1- 81 and alkaline phosphatase) indicated a loss of ESC pluripotency in the 1.0% ethanol group. ORMES-7 was more sensitive to effects of ethanol than ORMES-6. CONCLUSIONS: Estradiol appeared to increase sensitivity to ethanol in the ORMES-6 and -7 cell line. The morphological changes and labeling for pluripotency, proliferation and apoptosis demonstrated that ethanol affects how these early cells develop in culture, their differentiation state in particular. The effects of ethanol may be mediated in part through metabolic pathways regulating acetaldehyde formation, and while potentially accentuated by estradiol in some individuals, how remains to be determined.